Tradisi Rebutan Cacaran Samah Pada Piodalan Purnama Kadasa di Pura Panti Pasek Gelgel Aan Desa Adat Buleleng - Diatmika, I Dewa Gede Ngurah; Mastiningsih, Ni Nyoman (Prabha Vidya, 2024)
This study wanted to find out the philosophical basis of the smallpox samah tradition and to find out the series of implementation of the smallpox samah tradition on the full moon kadasa piodalan at Panti Pasek Gelgel Aan Temple, Peguyangan Banjar Environment, Astina Village, Buleleng Traditional Village. This study was a qualitative study. The results obtained by the researcher are as follows: (1) The philosophical basis of carrying out the smallpox seizure tradition is to express gratitude to Ida Shang Hyang Widhi Wasa for His blessings and His gifts are all given health and grace to his happy people, (2) Implementation of the smallpox snatch tradition samah which began with the arrival of Ida Batara lunga melasti to Segara Temple, when he arrived at the Panti Temple he was presented with the ayaban smallpox samah and after that the paridan/prasadam was contested by krame dadia as a form of gratitude for the gift given by Ida Shang Hyang Widhi Wasa. After completing the procession of Rabutan smallpox samah, it is continued with the implementation of the upright piodalan of this Gelgel Panti Pasek Temple.